Events of the eighth may 1945 Causes and consequences - lebbaz, tayeb (The Algerian Historical Journal, 2026)
I referred in this study to events of May 1945 happened in our country Algeria, alluding to political developments that the national movement had known prior to those incidents and to that national awareness that accompanied the Movement of Lovers of The Manifest and The Freedom founded in March 1944. France's colonial met its demands with all the mockery and denial. The national reaction through those events and slogans frightened the old people and the colonial authorities. Their response was the violent and the outrageous crime against the Algerian people. So i reffered to the course of these marches and their transformation into events from May to the important stage, which is the eighth day, when France blew up all its hatred, and revenge. And despite these events, this crime had consequences at the local and external levels. That had all of the effect in preparing for the launch of a national revolution that led to the realization of the algerian people's dream of Independence.